Global mid-upper arm circumference cut-offs for adults: a call to action. Issue 17 (26th December 2020) - Maalouf-Manasseh, Zeina; Remancus, Sandra; Milner, Erin; Fenlason, Lindy; Quick, Timothy; Patsche, Cecilie B; Bose, Kaushik; Collins, Steve; Ververs, Mija; Walia, Sonia; Escobar-Alegria, Jessica; Chung, Mei; et al.
Abstract : Since 2009, mid-upper arm circumference (MUAC) has become an accepted measure for screening children for acute malnutrition and determining eligibility for services to manage acute malnutrition. Use of MUAC has increased the reach and enhanced the quality of community-based management of acute malnutrition services. Increasingly, MUAC is also used to assess nutritional status and eligibility for nutrition support among adolescents and adults, including pregnant and lactating women and HIV and TB clients. However, globally recognised cut-offs have not been established to classify malnutrition among adults using MUAC. Therefore, different countries and programmes use different MUAC cut-offs to determine eligibility for programme services. Patient monitoring guidelines provided by WHO for country adaptation to support the integrated management of adult illness do not include MUAC, in part because guidance does not exist about what MUAC cut-off should trigger further action.